A Regional Project in Support of the SADC Cyber-Infrastructure Framework Implementation: Weather and Climate. (10th July 2019) - Bopape, Mary-Jane Morongwa; Sithole, Happy Marumo; Motshegwa, Tshiamo; Rakate, Edward; Engelbrecht, Francois; Archer, Emma; Morgan, Anneline; Ndimeni, Lwando; Botai, Joel
Early warning systems in the areas of weather and climate for supporting decision making and strategic intervention in key sectors (e.g. water, health, energy, disaster risk management, and agriculture) rely on the use of earth observations and numerical models that require supercomputing resources. Such resources are now primarily provided through High Performance Computing (HPC) facilities. As a result of a global increase in availability and accessibility of supercomputing HPC facilities, numerical models that can now be employed have become more complex. Furthermore, resolutions now used and achievable have increased significantly. The Southern African Development Community (SADC) Cyber-Infrastructure (CI) Framework aims to build increased capacity in regional research and education networks, data sharing infrastructure and trained human capital – to make efficient and effective use of the CI resources. Through the implementation of the regional CI framework and national initiatives, several member states in Southern Africa now have HPC facilities. The availability of this infrastructure in the region provides opportunities for domains, domain scientists and collaboration through research and development projects. For meteorology, this will support more local and regional weather and climate scientists. For meteorological services, this will mean increased in-house and in-country capacity to run models, with less reliance on external resources from developed countries. This paper discusses a regional weather and climate implementation project of the SADC CI.